Local incompressibility of fractional quantum Hall states at a filling factor of 3/2 - L. V. Kulik; V. A. Kuznetsov; A. S. Zhuravlev; V. Umansky; I. V. Kukushkin (Physical Review Research, 2020)
We studied neutral excitations in a two-dimensional electron gas with an orbital momentum ΔM=1 and spin projection over the magnetic field axis ΔS_{z}=1 in the vicinity of a filling factor of 3/2. It is shown that the 3/2 state is a singular point in the filling factor dependence of the spin ordering of the two-dimensional electron gas. In the vicinity of ν=3/2, a significant increase in the relaxation time (τ=13μs) for the excitations to the ground state is exhibited even though the number of vacancies in the lowest energy level is macroscopically large. The decrease in the relaxation rate is related to the spin texture transformation in the ground state induced by spin flips and electron density rearrangement. Based on the experimental data we believe that the 3/2 state is an example of locally incompressible fractional quantum Hall state.